PERSONALISMO POLÍTICO NOS ANOS CINQÜENTA (Revista de História Regional, 2007)
It is enquired into the relationship among the institutionalization of the political participation related to the creation of the national political parties and the political personalism linked to the idea of charismatic leader, in the context of the politics in Paraná in the late forties and middle fifties. The political party game is stood out, where it is used the issue of the corruption exposure and the involvement of the agrarian segments that demand the right to legitimate the land property. The conflict among those groups favoured the political-military articulation that put in check the Brazilian republic, in the following decade. The technique of the discourse analysis in the editorials and morning news from Curitiba and the government messages addressed to the Legislative Assembly of the State is used to typify the characteristics of the political personalist.